An Analysis of Imagery Found in Novel “The Midnight Library” by Matt Haig in 2020 - Al Amin, Merdeka Putri Khafidhotur Rohmah; Oktariza, Dodi; Efendi, Dedi (Universitas Muara Bungo, 2024)
This research aims to analyze the imagery in the novel